2011
DOI: 10.1124/dmd.111.042614
|View full text |Cite
|
Sign up to set email alerts
|

Identification of UDP-Glucuronosyltransferases Responsible for the Glucuronidation of Darexaban, an Oral Factor Xa Inhibitor, in Human Liver and Intestine

Abstract: ABSTRACT:Darexaban maleate is a novel oral direct factor Xa inhibitor, which is under development for the prevention of venous thromboembolism. Darexaban glucuronide was the major component in plasma after oral administration of darexaban to humans and is the pharmacologically active metabolite. In this study, we identified UDPglucuronosyltransferases (UGTs) responsible for darexaban glucuronidation in human liver microsomes (HLM) and human intestinal microsomes (HIM). In HLM, the K m value for darexaban glucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…In a similar experiment, Shiraga and colleagues showed kinetic benefit from low levels of BSA with UGT1A9 when evaluating darexaban. At 0.1% BSA, kinetic parameters similar to those obtained at 2% BSA were observed when corrected for the free fraction (Shiraga et al, 2012); however, the effects were most noticeable on the unbound K m and not the V max . …”
Section: Advances In Reaction Phenotypingsupporting
confidence: 53%
“…In a similar experiment, Shiraga and colleagues showed kinetic benefit from low levels of BSA with UGT1A9 when evaluating darexaban. At 0.1% BSA, kinetic parameters similar to those obtained at 2% BSA were observed when corrected for the free fraction (Shiraga et al, 2012); however, the effects were most noticeable on the unbound K m and not the V max . …”
Section: Advances In Reaction Phenotypingsupporting
confidence: 53%
“…Extrapolation of kinetic constants (CL int ) generated in the presence of bovine serum albumin or fatty acid-free human serum albumin has been reported to improve the prediction of in vivo hepatic clearance by glucuronidation for substrates of UGT1A9 and UGT2B7 via a decrease in K m values, with little or no effect on V max values. [24][25][26] In the case of darexaban glucuronidation by HLM, 5) 2% bovine serum albumin decreased the unbound K m value from 216 to 17.6 μM, and increased the unbound CL int value approximately 10-fold. The unbound K m is closely similar to that of recombinant human UGT1A9 (18.3 μM) in the presence of 2% BSA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings on UGT isoforms are consistent with the results of darexaban glucuronidation. 5) Human UGT isoforms are expressed in a tissue-specific manner. 20,21) Recent reports indicated that among UGT1A7, UGT1A8, UGT1A9, and UGT1A10, the mRNA expression level of UGT1A9 was highest and those of the other isoforms were extremely low or not detected in human liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations